2013
DOI: 10.1590/brag.2013.037
|View full text |Cite
|
Sign up to set email alerts
|

Resistência do algodoeiro à ferrugem tropical potencializada pelo silício

Abstract: ResumoEste trabalho teve como objetivo estudar o efeito do silício (Si) sobre componentes de resistência do algodoeiro à ferrugem tropical causada por Phakopsora gossypii. Plantas das cultivares BRS Buriti e FM 993 cresceram em solução nutritiva contendo zero (-Si) ou 2 mmol Si L -1 (+Si). A maior concentração foliar de Si aumentou o período de incubação e o período latente em 9% e 14,3%, respectivamente, reduziu a área pustular, a área abaixo da curva de progresso da ferrugem e a área abaixo da curva de progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
1
0
2
Order By: Relevance
“…PEREIRA et al (2009) found out that the application of potassium silicate to the leaves of coffee plants infected with Hemileia vastatrix led to an increase in the activities of quitinase (QUI) and glucanase (GLU) in intermediate stages of the infectious process. According to GUERRA et al (2013), the activities of these two enzymes may be related to the defense mechanisms of plants suppressed with Si, impeding the pathogen from entering, growing and colonizing the cells of the leaf tissue. In a previous study, Si enhanced the resistance to the coffee plant pathogen Cercospora coffeicola, with increase in cuticle thickness (POZZA et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…PEREIRA et al (2009) found out that the application of potassium silicate to the leaves of coffee plants infected with Hemileia vastatrix led to an increase in the activities of quitinase (QUI) and glucanase (GLU) in intermediate stages of the infectious process. According to GUERRA et al (2013), the activities of these two enzymes may be related to the defense mechanisms of plants suppressed with Si, impeding the pathogen from entering, growing and colonizing the cells of the leaf tissue. In a previous study, Si enhanced the resistance to the coffee plant pathogen Cercospora coffeicola, with increase in cuticle thickness (POZZA et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…O silício (Si) é um micronutriente com efeito pronunciado em plantas expostas a condições de estresse, bem como ao ataque de patógenos, podendo reduzir a severidade de doenças em algumas culturas (PEREIRA et al, 2009;CARRÉ-MISSIO et al, 2010;CRUZ et al, 2013;SANTOS et al, 2014). O aumento da lignificação da parede celular (CRUZ et al, 2012), a ativação de enzimas de defesa (quitinases, β-1,3-glucanases, peroxidases, polifenoloxidases, lipoxigenases e fenilalanina amônia-liases) (GUERRA et al, 2013) e a ação tóxica contra determinadas espécies de fungos (GOMES et al, 2011), são alguns dos efeitos promovidos pelo Si em plantas, que dificulta a infecção de fitopatógenos.…”
Section: Printunclassified
“…O silício é considerado um potencializador de resistência em plantas, devido à barreira mecânica que se forma nos tecidos pelo acúmulo deste mineral, além do incremento de compostos secundários que podem afetar o desenvolvimento de insetos e patógenos (ALCANTRA et al, 2010;GUERRA et al, 2013).…”
unclassified